2000
DOI: 10.1111/j.1348-0421.2000.tb02496.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Two‐Component Signal Transduction System Involved in Fimbriation of Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis, a periodontopathogen, is an oral anaerobic Gram-negative bacterium with numerous fimbriae on the cell surface. Fimbriae have been considered to be an important virulence factor in this organism. We analyzed the genomic DNA of transposon-induced, fimbria-deficient mutants derived from ATCC 33277 and found that seven independent mutants had transposon insertions within the same restriction fragment. Cloning and sequencing of the disrupted region from one of the mutants revealed two adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…The in vivo signal that triggers fimbrial expression is not known; however, it has been shown that expression of fimA, which encodes the fimbrillin protein subunit, is affected by environmental and nutritional parameters, since expression was repressed under elevated temperatures or hemin limitation (4,58,88). A two-component system (FimS-FimR) that regulates the expression of fimA was recently discovered (33,81,83), and it has been shown that the response regulator FimR controls expression at the level of transcription (65). Further studies of the function of PG0106 and the regulation of the expression of capsule are required to determine if the expressions of fimbriae and capsule are coordinated.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo signal that triggers fimbrial expression is not known; however, it has been shown that expression of fimA, which encodes the fimbrillin protein subunit, is affected by environmental and nutritional parameters, since expression was repressed under elevated temperatures or hemin limitation (4,58,88). A two-component system (FimS-FimR) that regulates the expression of fimA was recently discovered (33,81,83), and it has been shown that the response regulator FimR controls expression at the level of transcription (65). Further studies of the function of PG0106 and the regulation of the expression of capsule are required to determine if the expressions of fimbriae and capsule are coordinated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the molecular mechanism involved in the regulation of fimA expression is beginning to be understood. A two-component system (FimS-FimR) that regulates expression has been identified (Hayashi et al, 2000;Watanabe-Kato et al, 1998;Watanabe et al, 1996), and recently it was shown that the response regulator of this two-component system (FimR) controls the expression of these genes at the transcription level (Nishikawa et al, 2004). In regard to mfa1, expression of this gene has been shown to be affected by cell-to-cell contact with a variety of oral streptococci; either upregulation or downregulation was observed, depending on the species (Park et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the sequences upstream of the W50 fimS and the ATCC 33277 fimS are divergent. To confirm this, we designed a forward primer oligonucleotide (fimS_Seq-For) based on the published ATCC 33277 fimS locus sequence (17), repeated the PCR, and sequenced the amplicon. The result confirmed the data of Hayashi et al (17) and showed that the nucleotide sequences upstream of the fimS genes of the two strains are significantly different ( Fig.…”
Section: Genetic and Functional Organization Of Fimr And Fimsmentioning
confidence: 99%
“…It has been assumed that FimR (RR) and FimS (SHK) work in concert as a two-component regulatory system. Inactivation of either fimS or fimR in strain ATCC 33277 resulted in loss of fimbriation (17). Furthermore, FimR has been shown to directly regulate the expression of a limited number of genes, including pg2130, which is associated with FimA fimbriation (37), and mfa1, which encodes the minor fimbrillin Mfa1 (54).…”
mentioning
confidence: 99%
See 1 more Smart Citation